Use of Treponemal Screening Assay Strength of Signal to Avoid Unnecessary Confirmatory Testing. Issue 12 (December 2016) - Berry, Gregory J.; Loeffelholz, Michael J.
Abstract : Background: Our reverse syphilis testing algorithm consists of a treponemal IgG multiplex flow immunoassay (MFI) followed by both rapid plasma reagin titer and the Treponema pallidum particle agglutination (TPPA) test on specimens with a reactive MFI result. We report here the impact of a modified reverse algorithm, in which the strength of signal of the MFI is used to avoid unnecessary TPPA testing. Methods: The Bioplex syphilis IgG MFI was used as the syphilis screening assay, and specimens with equivocal (antibody index 0.9 or 1.0), or reactive (antibody index ≥ 1.1) results were further tested by rapid plasma reagin titer and TPPA test. We performed a retrospective, descriptive analysis of all specimens received for syphilis screening between January and May of 2014. A cost analysis was performed, taking into account labor and reagent expenses. Results: In our diverse patient population consisting of high-risk incarcerated persons, low-risk obstetrical/gynecological patients and high-risk miscellaneous clinic and inpatients, 430 (65%) of 665 MFI-positive specimens had antibody indices of 8 or greater. Greater than 99% of these specimens were reactive by the TPPA test. Avoiding TPPA testing of specimens with an MFI antibody index ≥8 would save over US 4800 annually in laboratory costs. Conclusions: The TPPA testing is unnecessary on specimens with MFI antibody indices ≥8. This would substantially reduce the TPPA testing volume and also reduce laboratory expenses. Abstract : Review of syphilis reverse algorithm test results found that 65% of reactive treponemal screens were strongly reactive and >99% of these were confirmed by a second treponemal test. Avoiding this unnecessary confirmatory testing would reduce laboratory costs.